PRODUCING HYDROGEN FROM NATURAL GAS BY THERMAL METHODS - Kincay, Olcay; Agustos, Haluk; Akbulut, Ugur (YILDIZ TECHNICAL UNIV, 2008)
Thermal methods like steam reformation (SR), partial oxidation (POx), autothermal reformation(ATR) and thermal decomposition (TD) are hydrogen producing methods which are studied on frequently. Increase of reformation efficiency by development of catalizors and decrement of reactor sizes are the main observed points. Also decrement of temperature and pressure values which are 700-1300 degrees C and 20-56 atm main target of case studies. For removeable and conventional usage, production of hydrogen with the cheapest and easy method is the main goal of improving these methods. On the other side; gasification, biochemical processes and electrolysis are also being used for producing hydrogen. The main problem is the lack of cheap electric energy source during electrolysis. Despite the biochemical processes'high costs and complex device requirements researches are being continued on, but stil not accaptable for applicaitons. It is known that gasification process comes true between the range of 800-2000 degrees C and on 40 atm pressure. Adding that process efficiency is 55% that a low reaction completion grade. Researches on gasification process are being continued on with more interest than biochemical processes. Keywords: Hydrogen production, steam reformer, partial oxidation, autothermal reforming, thermal decomposition.
Keywords: Hydrogen production; steam reformer; partial oxidation; autothermal reforming; thermal decomposition; SUSTAINABLE DEVELOPMENT; CATALYTIC PYROLYSIS; FUEL-CELLS; METHANE; ENERGY; DISSOCIATION; REACTOR; DECARBONIZATION; CONFIGURATION; Engineering